Interface nanocavities in poly (lactic acid) membranes with dispersed cellulose nanofibrils: Their role in the gas barrier performances. (12th August 2020) - Dickmann, M.; Tarter, S.; Egger, W.; Pegoretti, A.; Rigotti, D.; Brusa, R.S.; Checchetto, R.
Abstract: Poly (lactic acid) nanocomposites containing lauryl-functionalized cellulose nanoparticles were prepared by solution-casting method and structurally characterized. The gas transport process was studied in ~ 50 μm thick nanocomposite films with filler contents up to 12 vol% using He, 2 H2, N2 and CO2 as test gases. The gas permeability and diffusivity was evaluated by studying the permeation process using a specific mass spectroscopy technique in the temperature range from 298 K to 340 K in transient and stationary transport conditions. We present original diffusivity and permeability data as a function of the temperature together with the obtained values for the activation energy. Gas transport data were correlated with information on the nanocomposite free volume structure obtained by positron annihilation lifetime spectroscopy. The results indicate that the decrease of the gas barrier performances observed in nanocomposites with filler contents larger than ~ 5 vol% is due to an increased gas solubility caused by the formation of rigid cavities at the interface between the polymer matrix and micrometer-sized filler aggregations. Graphical abstract: Image 1 Highlights: Bio-nanocomposites gas barrier film of PLA with functionalized nanocellulose fibrils. Nanocavities at internal PLA-NC interfaces detected by PALS. Interface nanocavities degrade the gas barrier performances of bio-nanocomposites. Nanocavities act as additional solution sites hosting gas molecules. Gas transport data and activation energy values for neat and PLA nanocomposites.